The Influence of Fintech Payment and Financial Attitude on Financial Management Behavior: The Mediating Role of Self Control Among University Students FEB of Universitas Swadaya Gunung Jati - Sayyidah Firdaus Bahir; Mayaliza Mayaliza; Benny Dhevyanto (Greenation International Journal of Tourism and Management, 2026)
This study examines the influence of fintech payment and financial attitude on financial management behavior with self-control acting as a mediating variable among university studentss. The rapid development of financial technology has transformed the way individuals conduct financial transactions, particularly through digital payment systems such as e-wallets. This research employs a quantitative method using a survey approach. Data were collected from 387 studentss of the Faculty of Economics and Business at Universitas Swadaya Gunung Jati. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that fintech payment and financial attitude have a positive and significant influence on financial management behavior. Furthermore, self-control plays a significant mediating role in the relationship between fintech payment and financial attitude toward financial management behavior. These findings suggest that although financial technology offers convenience in financial transactions, self-control remains an important factor in supporting responsible financial behavior.